ANALYSIS OF CONSUMER BEHAVIOR IN ONLINE SHOPPING ISLAMIC PERSPECTIVE - Cinantya Sriyono Putri; Trisnaning Setya Sutjipto; Mohamad Sholeh (Universitas Airlangga, 2022)
The development of the digital era has triggered changes in consumer behavior in using technology for transactions. The emergence of online shops and marketplaces or online shopping sites has become one of the lifestyle choices of today's people to shop more practically and efficiently. However, in making purchases, a Muslim must remain obedient to the corridors and values of sharia. The purpose of this study is to investigate how consumer moslem behavior in online shopping obedient to guiding consumption principle in Islam. The method used in this research is a literature study which uses secondary data obtained from existing research and references. This study concludes that many previous study findings in majority moslems country such as Saudi Arabia, and Malaysia consumer moslem behaviour not obedient to the corridors and values of sharia as cited in Al-Quran dan As-Sunnah especially for avoiding israf (one of guiding consumption principle in Islam for not to consume excessively/hedonism). There is no difference found regarding the method of the buying (online/conventional). Both methods online and conventional buying behavior have a positive significant relationship in consuming with hedonism style. Muslim consumers must behave moderately where they do not act excessive consumption which leads to tabdhir (wastefullness) and also israf (excesiveness) or deficiency to lead to bukhl (miserliness) as Al-Quran and As-Sunnah cited.